Don't put the cart before the horse! - Mathis, Andre (Technical Centre for Agricultural and Rural Cooperation, 1997)
André Mathis, SBAM (Structure biologique pour une agriculture moderne), Lomé, Togo, writes to us with reference to 'Animal traction and small-scale mechanization' in Spore 69.'In Togo, animal traction has neither increased the yields nor the...